Prevalence of hypertension and diabetes mellitus at selected urban slums in Bangalore, India: a cross sectional study - M., Shivaraj B.; S., Vinay Kiran B.; S., Ranganath T. (International Journal Of Community Medicine And Public Health, 2017)
Background: Non communicable diseases are increasingly affecting urban slum people. This study was carried out by our institute at the behest of MOHFW, GOI, as a combined initiative with the Director of Health & Family Welfare Services, Karnataka State and Bruhat Bengaluru Mahanagara Palike. The objective of the study was to estimate the prevalence of Hypertension and Diabetes Mellitus among the residents of selected slums of Bangalore. To correlate the association of these morbidities with variables such as overweight/obesity. Methods:Cross-sectional study from October 2010-February 2011. Slums in and around the urban field practice area of Bangalore Medical College and Research Institute (BMCRI), Bangalore, India. One thousand three hundred and six (1306). Sampling method: All slums under BMCRI urban field practice area and few adjacent urban slums chosen at random. People aged more than 30years were pooled in by the local link health workers to the camps. A pre-tested, semi-structured questionnaire was used. Blood pressure (Using sphygmomanometer) and random blood sugar (Glucometer) were measured. Hypertension was classified as per JNC VII criteria and Diabetes as per the ADA guidelines. Results: 1306 subjects participated at the survey. 255 were males and 1051 were females. Average age being 51.88+20 years. 209 (16%) subjects were using tobacco in any forms. 88 (6.7%) subjects had family H/O Diabetes and 46 (3.5%) had Hypertension in the family. 417 (31.92%) were found to be having Diabetes and 247 (18.9%) were diagnosed as hypertensives. 147 (11.2%) subjects were having both Diabetes and hypertension. Conclusions:The reason for high prevalence of the morbidities seemed to be lack of awareness regarding health care seeking and lack of compliance to treatment. Subjects with diagnosed morbidities were given health education and referred to higher center for further management.